SOLUTION
For a line to be perpendicular to another line, product of thier gradient must be -1.
if the gradient is given as
![\begin{gathered} m_{1\text{ }}andm_{2\text{ }},\text{ then} \\ m_1m_(2=-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jho5ll3h27wbleavc14jcv0zcmt0es0sy9.png)
Then given the line
![y=(6)/(7)x+2](https://img.qammunity.org/2023/formulas/mathematics/college/alomshk6jl15fs3sitbmraiw6c5daf9buw.png)
The gradient of the line is the coefficient of x using the expression
![\begin{gathered} y=mx+c \\ m=Gradient \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tbjknkhie71ihi5buwk8ni6sw7evpiy5nn.png)
Hence, we have
![m_1=(6)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/fcs4e6h2ox6zhhl1m8br3r0soiq8jkfsnk.png)
Then, using
![\begin{gathered} m_1m_2=-1 \\ m_2=(-1)/(m_1) \\ m_2=-1*(7)/(6)=-(7)/(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ybmf3uiflgd4wfuqe1ydveqag4q133e1jt.png)
Given the point (-6,4), the line perpendicular will be having the equation
![\begin{gathered} y-y_1=m_2(x-x_1) \\ \text{where }y_1=4\text{ and x}_1=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d17g526ptaqv7f6klik1qrye2g33ui75ki.png)
Then we obtain
![\begin{gathered} y-4=-(7)/(6)(x-(-6)) \\ y-4=-(7)/(6)x-7 \\ y=-(7)/(6)x-7+4 \\ y=-(7)/(6)x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yeoc4w5hq0lx0mjvaaa36t30mk832nx0py.png)
Therefore the equation perpendicular to this line is given as y=-7/6x - 3
![y=-(7)/(6)x-3](https://img.qammunity.org/2023/formulas/mathematics/college/tgkpxh4r2yse7z6iluyfu5kironvwir3q5.png)
Then the equation parallel to the same line will have the same gradient
![m_1=m_2=(6)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/m71drmhb72k0dtbe2tk3b5ogu5p0re4p8w.png)
Then the equation parallel passing through the point (-6,4) will be
![\begin{gathered} y-4=(6)/(7)(x-(-6)) \\ y-4=(6)/(7)(x+6) \\ y-4=(6)/(7)x+(36)/(7) \\ y=(6)/(7)x+(36)/(7)+4 \\ y=(6)/(7)x+(64)/(7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ik8fzybmlvbynl41qe2palyqdecb525vuv.png)
The equation of the line that is parallel to this line and passes through the point (-6, 4) will be y=6/7x+64/7
![y=(6)/(7)x+(64)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/mvjtd9vujcbulh5ufwtcoznlexil4ikcvx.png)